(3eONd dEOGQI GdCYeGd (B: s (3eWHhYI HjOGZhLjI ehLgI dWdHI GdSfI GdChdi (B-(3LPY eTJQc(B- (3djSGfS (B-LMD- / s - (3JGQRj, BefIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3WHjYI Yde GdEOGQI , GdeOjQ h GdYedjI GdEOGQjI , JWhQ GdacQ GdGOGQj , GdhXGFa GdGOGQjI (B.s
(3eQGLY U(B. 110s
Keywords: (3GOGQI GdGYeGds